Conversion of Cu2+-polluted biomass into Cu2+-based metal-organic frameworks antibacterial material to achieve recycling of pollutants. (10th July 2020) - Yang, Jianwei; Wu, Jia; Feng, Pu; Li, Yanming; Tang, Xiuzhen; Chen, Jinli; Lin, Baofeng
Abstract: The widespread heavy-metal-polluted biomass adsorbents produced by biosorption are difficult to deal with. It is a challenge to develop simple and efficient method for the recovery and utilization of polluted biomass adsorbents. In this work, biomass adsorbents of polyethyleneimine/cellulose/sodium alginate (PCS) were synthesized by chemical crosslinking, and then PCS adsorbed Cu 2+ to simulate Cu 2+ -polluted biomass adsorbents (PCS–Cu 2+ ). After that PCS-Cu 2+ was converted into PCS@Cu3 (BTC)2 (PCS@HKUST-1) composite antibacterial material by in-situ growth, i.e. the growth of PCS@HKUST-1 was carried out with the "locked" Cu 2+ ions which was derived from PCS-Cu 2+, as the nodes of HKUST-1 growth. The results showed that approximately 88% of Cu 2+ ions in PCS-Cu 2+ were switched as the nodes of HKUST-1. Moreover, the converted product of PCS@HKUST-1 exhibited antibacterial activity much better than those of PCS and PCS-Cu 2+, its antibacterial efficiency against Escherichia coli up to 98.14%, while that of PCS and PCS-Cu 2+ were only 2.63% and 4.77%, respectively. Overall, this study not only provides a novel eco-friendly recyclable method for heavy metal polluted biomass adsorbents, but also develops a good bacteriostatic material. Graphical abstract: Schematic illustration of in-situ growth routes for recyclable of Cu 2+ -polluted biomass. Image 1 Highlights: Converted Cu-polluted PCS into PCS@HKUST-1 avoid secondary pollution. Good recyclability and 88% of Cu 2+ switched as the nodes of HKUST-1. PCS@HKUST-1 against Escherichia coli was 98.14%.